Sensors Proceedings of the Second National Conference on Sensors, Rome 19-21 February, 2014 - Compagnone, Dario.; Compagnone, Dario.; Baldini, Francesco.; Baldini, Francesco.; Di Natale, Corrado.; Di Natale, Corrado.; Betta, Giovanni.; Betta, Giovanni.; Siciliano, Pietro.; Siciliano, Pietro. (Lecture Notes in Electrical Engineering,, 2015)
This book contains a selection of papers presented at the Second National Conference on Sensors held in Rome 19-21 February 2014. The conference highlighted state-of-the-art results from both theoretical and applied research in the field of sensors and related technologies. This book presents material in an interdisciplinary approach, covering many aspects of the disciplines related to sensors, including physics, chemistry, materials science, biology and applications. ·         Provides a selection of the best papers from the Second Italian National Conference on Sensors; ·         Covers a broad range of topics relating to sensors and microsystems, including physics, chemistry, materials science, biology and applications; ·         Offers interdisciplinary coverage, aimed at defining a common ground for sensors beyond the specific differences among the different particular implementation of sensors.